Investigation of Anisotropic Permeability and Porosity of CJRM considering Different Confinement Loading Pressures. (3rd July 2020) - Chao, Zhiming; Ma, Guotao; Hu, Xiewen; Zhu, Yuzhe
Abstract : An innovative method is proposed to prepare artificial columnar jointed rock masses (CJRM) with different columnar dip angles, and laboratory physical model tests are conducted to investigate anisotropic permeability and porosity characteristics of the prepared artificial CJRM. In the physical model experiment, permeability and porosity of artificial CJRM with different columnar dip angles is measured during three times cyclic loading and unloading of confinement pressure. Based on the results of the laboratory model tests, the Equivalent Continuum Media Model was applied to analyse anisotropic permeability of CJRM. The main conclusions are summarized as follows. In the first loading phase of confinement pressure, the impacts of confinement pressure on the anisotropic permeability of artificial CJRM, porosity, and the major and minor principle permeability coefficients (PPCs) are significant, while in the following stages of confinement pressure loading and unloading, the change of them is small, with stable value. Permeability of artificial CJRM gradually increases with rise of columnar dip angle, and the permeability anisotropy of artificial CJRM under low confinement pressure is higher than that under low confinement pressure.